Psychological characteristics of internet addiction in students in problem life situations (COVID-19, war) - CHUYKO, Halyna; CHAPLAK, Yan; KOLTUNOVYCH, Tetiana (Revista Românească pentru Educaţie Multidimensională, 2024)
The relevance of this research lies in the fact that the number of Internet addicts in the world is constantly growing (the premise of which we consider the possibilities of Internet content that open up to a person in the virtual space), and the situation can turn into a public health problem. The purpose of the article is to carry out a theoretical analysis of the phenomenon of Internet addiction and, based on it, conduct an empirical study of Internet addiction of students, its connection with their personal traits and their satisfaction with life in difficult life situations: during the COVID-19 pandemic (n=88) and war (n=87). The research used the following methods: Internet Addiction Test (K. Young), CIAS, Chen-Internet- Addiction-Scale (S.-H. Cnen), Techniques for diagnosing predisposition to 13 types of addictions (G.V. Lozova), Test T. Leary, Questionnaire “Life Satisfaction Index” (B. Neugarten, R. Havighurst, Sh. Tobin), Oxford Happiness Inventory, OHI. Mathematical processing of research results was carried out using statistical package SPSS 17.0. The analysis of approaches to the understanding of Internet addiction by scientists leads to the conclusion that it is a behavioral deviation that manifests itself in a person’s excessive spending of time in the Internet space due to reluctance to return to real life; this is exactly information addiction. The main symptoms of Internet addiction: the tendency of an individual to choose being on the Internet before any other types of his activity; a change in his/her state of consciousness, a gradual increase in the time spent on the Internet, the lack of an objective assessment of the negative consequences of Internet addiction. As a result of the study, it was found that: Internet addiction can be combined with other types of addiction, Internet addicts are characterized by certain types of attitude towards others and a lack of feeling of satisfaction with life; Respondents who are less dependent on the Internet tend to positively evaluate themselves, be consistent in achieving their goals, fall into other addictions less often, and activate situationally necessary types of attitude towards others.
Keywords: Internet, Internet-addiction, peculiarities of Internet addiction, students, war situation, COVID-19.